ANALISIS PENDAPATAN DESA TERHADAP ALOKASI BELANJA DESA PADA DESA MUARA KILIS KECAMATAN TENGAH ILIR KABUPATEN TEBO - Irwansyah, Abdulrahim; Novi Mubyarto; Khairiyani (EKSYA : Jurnal Ekonomi Syariah, 2022)
This research is entitled Analysis of Village Income Against Village Expenditure Allocation in Muara Kilis Village, Tengah Ilir District, Tebo Regency. This research aims (1). To explain village income and village expenditure in Muara Kilis village in 2020. (2). To explain the Village Expenditure Allocation based on the realization of Village Income in Muara Kilis Village in 2020. The results of this study are: (1) Muara Kilis Village Revenue realized in 2020 consists of 1) State Revenue and Expenditure Budget Allocation (Village Fund) of Rp. 980,390,000. 2) Share of Regional Taxes and Regional Levies for Regency/City, amounting to Rp. 18,245,614. 3) Village Fund Allocation of Rp. 622,447,000. 4) Financial Assistance from the Provincial APBD and Regency/City APBD of Rp. 60,000,000. With a total village income of Rp. 1,681,082,614. Meanwhile, Muara Kilis Village expenditure in 2020 is allocated to five sectors, namely, 1) Village Government Implementation of Rp. 621,492,614, 2) Village Development of Rp. 293.957.300, 3) Village Community Empowerment of Rp. 59,950,700, 4) Community Development of Rp. 39,200,000, and 5) Disaster Management and Emergency Expenditure of Rp. 666,482,000. With a total village income of Rp. 1,681,082,614. (2) In Muara Kilis Village, with a total income of Rp. 1,681,082,614 has not been able to realize income from 3 other sources of income, namely from Village Original Income, Grants from third parties, and other legitimate income. As can be seen in the data above, which shows that the income from the three sources is 0% or Rp. 0 rupees. Meanwhile, Muara Kilis Village Expenditures are by Government Regulation Number 47 of 2015, which must be used with the following provisions: At least 70% (70% or more) of the village's total spending budget will be used to fund the village administration. Implementation of village development, village community development, and strengthening of rural communities (4 regions). Up to 30% (?30%) of the village's total budget will be used for the four items. 1) bonds and allowances for village mayors and village officials, 2) village government obligations, 3) allowances and obligations, village advisory boards, and 4) incentives for Rukun's neighbors.